Glucocorticoids prescribing practices in systemic sclerosis: an analysis of the EUSTAR database - Iudici, Michele; Mongin, Denis; Siegert, Elise; Carreira, Patricia E.; Distler, Jörg; Henes, Joerg; Zanatta, Elisabetta; Hachulla, Eric; De Luca, Giacomo; Mueller, Carolina De Souza; Santiago, Tania; Tandaipan, Jose-Luis; et al. (Rheumatology, 2022)
Objectives To estimate the prevalence of long-term exposure to glucocorticoids (GCs) and to identify factors associated with, and variations in prescribing practices over time and across recruiting countries. Methods We included patients with SSc having a visit recorded in the EUSTAR database from January 2013 onward. We analysed the prevalence and the main features of GCs users, their exposure to GCs over time, and their GCs dosages. Multivariable linear regression was used to analyse the factors identified as associated with GCs intake duration. Time trends, and variations in GCs utilization across recruiting countries were explored. Missing data were imputed using multiple imputation with chained equations. Results The 9819 patients included were mostly females (85%), the majority had lcSSc (73%), and the median age was 58 years. At baseline, 34% of patients (n = 2769/8109) (48% dcSSc vs 29% lcSSc) were on GCs, and the median dose was 7.5 mg/day. GCs users were more frequently males and anti-Scl70 positive, and more commonly had dcSSc and more severe disease. On average, GCs users spent 25% of their follow-up time (median 33.2 months) on GCs, with no significant between-subsets difference. Notably, 33% (n = 971/2959) and 22% (n = 647/2959) of patients followed up for >1 year had received GCs for >6 and >12 months, respectively. Multivariable analysis showed that patient and disease characteristics poorly explained the variability in GCs exposure (adjusted-R-2 = 0.06, P < 0.001). GCs utilization varied within and across countries, and gradually decreased over time (36% in 2013 vs 23% in 2018). Conclusions GCs are widely and long-term prescribed in SSc, with significant between-countries and within-country differences. A gradual decrease in their utilization has been observed.
CRIS-Team WoS Importer:2022-10-28